Efektivitas Model Blended Learning terhadap Pemahaman Menulis Cerpen dalam Pembelajaran Daring - Awaliyah Rohmatul; Mochamad Arifin Alatas (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research is motivated by the lack of students' understanding of the ability to write short stories. This study aims to see the effectiveness of the blended learning model on the understanding of short story writing in online learning carried out in class XI SMA Darul Ulum Kepohbaru Bojonegoro. This research method is a quantitative research method with a descriptive approach. The technique used in this research is the distribution of questionnaires and interviews. The data obtained to see the effectiveness is through student learning outcomes to write short stories and student response questionnaires about the blended learning model. The research data were then analyzed using the normality test and linearity test. From the results of the research, it is known that the normality test value of the results of writing short stories has a significance value of 0.026 > 0.05, while the results of student responses have a significance value of 0.679 > 0.05. Then. In the linearity test, the significance value is 0.129 > 0.05, meaning that the blended learning model is effectively used for understanding short story writing.